Substitute t = 3 and t = 6 to determine if the two expressions are equivalent. 3 (2 t + 5) 6 t + 15 Which statements

Question

Substitute t = 3 and t = 6 to determine if the two expressions are equivalent.

3 (2 t + 5) 6 t + 15

Which statements are true? Select the three correct answers.
The value of both expressions when t = 3 is 33.
The value of both expressions when t = 3 is 23.
The value of both expressions when t = 6 is 41.
The value of both expressions when t = 6 is 51.
The two expressions are equivalent.
The two expressions are not equivalent.

in progress 0
Thiên Di 6 months 2021-07-25T20:50:03+00:00 2 Answers 100 views 0

Answers ( )

    0
    2021-07-25T20:51:07+00:00

    Answer

    Option A: The value of both expressions when t = 3 is 33.

    Option D: The value of both expressions when t = 6 is 51.

    Option E: The two expressions are equivalent.

    Step-by-step explanation

    ♡ ∩_∩

    („• ֊ •„)♡

    ┏━∪∪━━━━┓

    ♡ good luck 。 ♡

    ┗━━━━━━━┛

    0
    2021-07-25T20:51:07+00:00

    Answer:

    If t= 6

    3 (2 x 6 + 5) 6 x 6 + 15

    3 (12+5) 36 + 15

    3 x 17 =51

    = 51

    The value of both expressions when t=6 is 51

    When t = 3

    3(2 x 3 + 5) 6 x 3 + 15

    3 (6 +5) 18 + 15

    3 x 11 =33

    = 33

    The value of both expressions when t= 3 is 33

    Step-by-step explanation:

    Step-by-step explanation:

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )